Sosialisasi Budidaya Ikan Air Tawar Bagi Mahasiswa Konsentrasi Ekonomi Pertanian - Sarlota Ratang; Siti Aminah; Hans Kaiway; Yundy Hafizrianda (UNIVERSITAS CENDERAWASIH, 2019)
Freshwater fish farming is one of the livelihoods of people around Sentani Lake, by seeing the very proud of potential, it is very necessary to make a closer introduction/socialization on how to do business in the field of inland fisheries to students of Agricultural concentration. Not only the theory obtained at college but couple with practice or go to the field could be necessary for students.